Unemployment in Europe: what does it take to bring it down? - Boeri, Tito; Jimeno, Juan F. (Frankfurt am Main, 2015)
"Unemployment in Europe is not only “too high”. It is also too different across countries, belonging to a monetary union. In this paper we i) document this increasing heterogeneity, ii) try to explain it, and iii) draw from our diagnosis indications as to the appropriate set of policies to reduce unemployment and labour market disparities. Our analysis suggests that the divergence in labour market outcomes across Europe is the by-product of interactions between, on the one hand, the size and nature of shocks, and, on the other hand, country-specific labour market institutions. We argue that EU policy co-ordination and conditionality during the Great Recession and the Euro debt crisis did not properly take into account these interactions. We also propose a change in the European policy approach to fight unemployment."